Hubungan Pengetahuan Ibu Hamil dengan Gingivitis Selama Kehamilan di Puskesmas Bahodopi Kabupaten Morowali - Aulyah, Dwi Rezky; Pariati; Usman, Faradillah; Jauharuddin, Arfiah; Sundu, Suciyati (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Pregnant women are a group that is vulnerable to various diseases, especially dental and oral diseases. Pregnancy is a process of change in order to continue offspring that occurs naturally, producing a fetus that grows in the mother's womb, the growth rate and size of the fetus according to gestational age. The aim of this study was to determine the relationship between the level of knowledge of pregnant women regarding gingivia at the Bahodopo health center, Morowali district. This type of research is analytical survey research. The research design used was quantitative with a cross sectional approach. The sampling technique in this research was non-probability sampling using accidental sampling of 34 people. The results of this study showed that 15 respondents had good knowledge of pregnant women, 14 respondents had sufficient knowledge and 5 respondents had poor knowledge. Pregnant women with good knowledge had gingivitis in the severe category as many as 7 people (46.7%) and mothers with sufficient knowledge had gingivitis in the moderate category as many as 7 people (50%) and pregnant women who had less knowledge had deep gingivitis. 4 people in the medium category. Based on the results of the chi-squared relationship test, it is known that the p-value is 0.244 > 0.05, which means that knowledge of pregnant women during pregnancy does not have a close relationship between knowledge and gingivitis.